Elaboración de una guía detallada de precios para profesionales en el área de Diseño gráfico en Ecuador - Díaz, José D. (2021)
This research aims to determine if the students of the last level of graphic design in Ecuadorian universities are familiar with how to bill a service. They asked a series of open questions, in the same way if they knew and used a price guide. In addition, according to the results of the study, graphic design is not recognized in Ecuador. In the end, a prototype pricing table was developed based on the services they provide in various industries.